Penentuan Jumlah Tenaga Kerja Yang Optimal - Bakhtiar E, Moh Arif; Susilo, Hendro (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2020)
Abstract— Construction projects are a series of activities that have a time at the beginning and end time with the aim of realizing the idea into a physical form or building. Labor is one of the important resources, because often the supply is limited, both because of quality and other things. With a good workforce management impact on the completion of construction projects. But in the construction phase, contractors often experience many problems related to the construction project's labor allocation. This study uses the help of Microsoft Project 2007 application to create a network of Precedence Method Method (PDM) methods, then generate a bart chart for the preparation of a project implementation schedule or S schedule (time schedule) so that a histogram can be obtained after a leveling process is needed. The results of data analysis with a case study of the Bank Mandiri Development Project Palembang Office Building, it can be concluded leveling shows that the workforce needs are far less than previously planned. The number of planner workforce based on planner consultant data and reports is 8681 people and from the research results based on data processing the leveling process is only 7754 people. Keywords—: S curve; labour, histogram; Microsoft Project.